Effect of ply thickness and ply level hybridization on the compression after impact strength of thin laminates. (June 2019) - Sasikumar, A.; Trias, D.; Costa, J.; Blanco, N.; Orr, J.; Linde, P.
Abstract: There is a lack of research available on how thin laminates respond to impact and post impact loads, even though thin structures are used in present-day aircrafts. This experimental paper employs thick, standard and thin uni-directional plies to investigate the effect ply thickness has on thin laminates on their impact and compression after impact (CAI) response. Further, we propose two hybrid laminates where thick or standard plies are mixed with thin plies, respectively, in an effort to improve the CAI strength of thin laminates. Results reveal that, contrary to thick laminates, thin laminates made of only thin plies exhibit extensive fibre failure, leading to a considerably reduced CAI strength. Moreover, the hybrid laminate where thick 0° plies are mixed with thin plies improves the CAI strength by 40% over the thin ply baseline laminate. Thus, hybridization with thin laminates appears to be an economic prospective in terms of improving damage tolerance.